Capacitance reduction of pulse voltage generator by using series voltage compensator. Issue 3 (10th January 2019) - Takahashi, Yuki; Iijima, Ryuji; Isobe, Takanori; Tadano, Hiroshi; Yamazaki, Choji; Hasegawa, Chihiro
Abstract: This paper proposes a new configuration of a pulse voltage generator, which can be applied to the klystron modulator for a large‐scale accelerator. The voltage generator consists of a conventional capacitor discharge type pulse voltage generator and series cascaded voltage compensators. By using the voltage compensators, higher voltage fluctuation of the bank capacitor is acceptable; therefore, its capacitance and the dimensions of the capacitors can be low. This paper discusses the control strategy of the voltage compensators and thyristors for DC voltage supply for the highly fluctuating capacitor voltage, and demonstrates this by a laboratory‐scale experimental setup.